THE BIOLOGICAL EFFECTIVENESS OF GIBBERELLIC ACID SEEDS SOAKING AND FOLIAR TO ABSCISIC ACID IN THE GROWTH , ANISE OIL YIELD AND ITS CHEMICAL CONTENT - B. I. Mustafa, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was carried out during two winter season 2013, 2014 at the field of the Department of Field Crops, College of Agriculture, University of Baghdad, to study the effect of seeds soaking with Gibberellic acid and foliar with Abscisic Acid on the growth, yield, and content of Anise oil seeds using factorial experiment within RCBD design with three replicates. The seeds was treated within GA3 were soaked with two concentrations of 30, and 60 mg. litter-1 in addition to without soaking and the code has been B0 , B1 , B2 overlapped these transactions with two concentrations of Abscisic Acid 3, and 6 mg. litter-1 in addition to without foliar A0 , A1 , A2The seeds to be treated with GA3 are soaked for 24 hours prior of cultivation in the platelets according to the studied treatments, plants treated with Abscisic Acid were sprayed, at the height of the vegetative stage was 4-6 leaves and repeated foliar after 30 days, treated plants A0B2 (sprayed with distilled water only with 6 mg. litter-1) achieved the highest values for both seasons: The plant hight (88.93,90.33) cm, number of leaves (64.71,70.50), number of branches (30.56,43.66), wet weight (915.70,1030.17) g, dry weight (221.67,256.80) g,Content of chlorophyll (70.46,71.83) mg, Content of carbohydrates (68.89,74.86)%, Content of auxin (56.46,64.10)%, Content of gibberellin (103.30,109.16)%, Content of volatile oil (4.03,5.36)%, Yield of volatile oil (56.06,96.98) L-1.